Produksi Cairan Penyanitasi Tangan Herbal untuk Mengatasi Kelangkaan Produk Komersial di Kota Salatiga - Dhanang Puspita; Kristiawan Prasetyo Agung Nugroho; Kukuh Pambuka Putra; Fiane de Fretes (AgriHealth, 2022)
The beginning of the Covid-19 pandemic in Salatiga began in March 2020 which caused a shortage of commercial hand sanitizer supplies. The production of herbal hand sanitizer is a solution for commercial products. This community service activity aims to produce herbal hand sanitizer to overcome the scarcity of hand sanitizer in Salatiga City. The method used is a laboratory experiment with stages; plant inventory, production of hand sanitizer, and antimicrobial testing. Inventory is done by collecting library-journal information, then conducting a field survey. The production of sanitizing liquid is carried out by laboratory experiments to get a good formulation. Antimicrobial test was carried out by diffusion technique. Herbal hand sanitizing liquid made from green betel, red betel, citronella, and star anise and the results of antimicrobial analysis have medium inhibition. A total of 1041.5 l of herbal hand sanitizer that have been distributed to the public free of charge. Testimonials from people who use herbal hand sanitizer are that they are not dry on the hands, not sticky, and have a fragrant aroma. The resulting product is still below commercial products on the market, but still has effectiveness in killing microorganisms.